Dinner with Griselda - Lyman-Dixon, Anthony (Petits Propos Culinaires, 2013)
The author speculates on what could one expect if invited to supper by Griselda, the patient Griselda who was the subject of Boccaccio’s final story in The Decameron, who was then the heroine of ‘The Clerk’s Tale’ in Chaucer, and who also figures in Petrarch and Perrault.